Selective uptake of high-density lipoprotein-associated cholesteryl esters by human hepatocytes in primary culture - Rinninger, Franz; Brundert, May; Jäckle, Stefan; Galle, Peter R.; Busch, Christoph; Izbicki, Jakob R.; Rogiers, Xavier; Henne-Bruns, Doris; Kremer, Bernd; Broelsch, Christoph E.; Greten, Heiner (Hepatology, 1994)
High-density lipoprotein cholesteryl esters are taken up by many cells without simultaneous uptake of high-density lipoprotein apolipoproteins. This selective uptake was investigated in human hepatocytes in primary culture. Human high-density lipoprotein-3 (density, 1.125 to 1.21 gm/ml) was radiolabeled in both its apolipoprotein and in its cholesteryl ester moiety; uptake of these high-density lipoprotein3 tracers by hepatocytes was investigated. Apparent high-density lipoprotein3 particle uptake as measured with the cholesteryl ester tracer was in excess of that from the apolipoprotein tracer, indicating selective uptake of high-density lipoprotein3 cholesteryl esters by hepatocytes. This selective uptake is a regulated pathway in hepatocytes, as demonstrated by an inverse relationship between cell cholesterol and the rate of selective uptake. Studies on the mechanism of selective uptake have used inhibitors such as monensin, chloroquine, heparin, and a monoclonal antibody directed against low-density lipoprotein receptors. These experiments provide no evidence for a role of cell-secreted apolipoprotein E, endocytosis or retroendocytosis in selective uptake. The intracellular fate of high-density lipoprotein3-associated cholesteryl esters was investigated with [3H]cholesteryl oleatelabeled high-density lipoprotein3. Hepatocytes hydrolyzed [3H]cholesteryl oleate internalized from labeled high-density lipoprotein3; this catabolism was not inhibited by the presence of chloroquine. In parallel hepatocytes were incubated with [3H]cholesteryl oleate-labeled low-density lipoprotein. Cells hydrolyzed [3H]cholesteryl oleate taken up with low-density lipoprotein; however, this hydrolysis was inhibited by chloroquine, indicating lysosomal low-density lipoprotein cholesteryl ester catabolism. These experiments show that high-density lipoprotein3 cholesteryl esters selectively taken up by hepatocytes are hydrolyzed independently from the classical lysosomal catabolic pathway. The question was addressed if selective uptake mediates a net mass uptake of cholesterol rather than an isotope exchange phenomenon. Incubation of hepatocytes with high-density lipoprotein-3 suppressed endogenous sterol synthesis from sodium [14C]acetate. Hepatocytes were incubated in the presence of high-density lipoprotein3; medium cholesteryl esters decreased as a result of incubation with hepatocytes. These results show a net mass delivery of high-density lipoprotein cholesteryl esters to hepatocytes. In conclusion, the pathway for selective uptake of high-density lipoprotein cholesteryl esters could be demonstrated in human hepatocytes in primary culture. A role for selective uptake in high-density lipoprotein-mediated cholesterol delivery to the liver in human beings in vivo is proposed. (HEPATOLOGY 1994;19:1100-1114.)